Business process re-enginering of tourism e-marketplace by engaging government, small medium enterprises and tourists - Kadek Cahya Dewi; Ni Wayan Dewinta Ayuni (Bulletin of Electrical Engineering and Informatics, 2021)
Not all tourism actors in Indonesia had utilize the e-marketplace. Therefore, one of the Indonesian government's focus is to improve the tourism business process model through e-marketplace based system. The research purpose was to re-engineer the business process of tourism e-marketplace by engaging government, small medium enterprises (SMEs) and tourists. The research used the mixed method approach that conducted by modifying The McKinsey BPR methodology. As the result, this research adding two novel aspects to the previous research which are "role" and "activities". The new tourism e-marketplace business model proposed three kinds of role, namely: (1) government, (2) SMEs, and (3) tourists. This model also introduced activities including catalogue, finance, inventory management, collaboration, order fulfilment and customization. The proposed model was implemented and can be found in http://gonusadua.com. TELOS feasibility study was conducted to evaluate the model and found the final score of 8.3. It can be concluded that this model was feasible to develop and provide benefits for the government, SMEs, as well as the tourist. Beside had a contribution in built a new model of tourism e-marketplace, the research had also constructed a new tourism e-marketplace system with some improvements on the business model.